Language learning strategies used by male and female students in learning speaking - Ayu Suhesti; Kasmaini Kasmaini; Ildi Kurniawan (Journal of English Education and Teaching, 2022)
This research aim at finding out language learning strategies used by male and female students in the fourth semester of the English education study program at Universitas Bengkulu. This research is descriptive quantitative. The population of this research is 117 students of the fourth-semester of English education study program at Universitas Bengkulu in the 2020/2021 academic year, and 52 students are taken as the sample by using purposive sampling. The data were collected by using a questionnaire. The questionnaire consisted of 31 items which represent 6 categories of learning strategies adapted from Strategy Inventory for Language Learning (SILL) version 7.0 proposed by Oxford. The collected data is analyzed by using Microsoft Excel 2007 and SPSS version 23. The results showed both males and females used all strategies category. Those are memory, cognitive, compensation, metacognitive, affective and social strategy. The dominant strategy used by male students are cognitive and compensation strategy (M=3.67), while the dominant strategy used by female students is metacognitive (M=3.74). Based on the result, there is no significant difference between males and females in using language learning strategies. Finally, the researchers suggest for lecturers who can use this research as information to design lesson plans in their speaking class. It is also suggested for students to use learning strategy in learning speaking more properly, the students have to find appropriate strategies that should be applied in learning speaking and for next researchers who will conduct the same topic of this research should make the next research more detailed information by involving other instruments.